1998
DOI: 10.1111/j.1471-0528.1998.tb10234.x
|View full text |Cite
|
Sign up to set email alerts
|

The outcomes of pregnancy in women exposed to newly marketed drugs in general practice in England

Abstract: Objective To determine the proportion and nature of congenital anomalies in babies born to Design Non-interventional observational cohort studies. MethodsThe women were identified in confidence by the Prescription Pricing Authority. The doctor was sent a questionnaire to determine clinical events, including pregnancy, occurring after the drug was dispensed. A supplementary questionnaire determined the outcome of each reported pregnancy.women exposed to newly marketed drugs during the first trimester.Setting Ge… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
62
0

Year Published

1999
1999
2016
2016

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 128 publications
(63 citation statements)
references
References 14 publications
1
62
0
Order By: Relevance
“…No congenital anomalies were observed among 11 births exposed to GBP in the first trimester. 171 One RCT of rapid versus slow initiation, 173 eight uncontrolled trials (four in epilepsy (n = 2986) [174][175][176][177] and four in bipolar disorder (BPD) (n = 60), 178,181,451 four open-label extension studies in epilepsy [182][183][184][185] and one uncontrolled cohort study of patients with spinal cord injury 186 were identified. These studies are summarised in Appendix 25, Table 100.…”
Section: Gabapentinmentioning
confidence: 99%
See 2 more Smart Citations
“…No congenital anomalies were observed among 11 births exposed to GBP in the first trimester. 171 One RCT of rapid versus slow initiation, 173 eight uncontrolled trials (four in epilepsy (n = 2986) [174][175][176][177] and four in bipolar disorder (BPD) (n = 60), 178,181,451 four open-label extension studies in epilepsy [182][183][184][185] and one uncontrolled cohort study of patients with spinal cord injury 186 were identified. These studies are summarised in Appendix 25, Table 100.…”
Section: Gabapentinmentioning
confidence: 99%
“…171,188 These reports are summarised in Appendix 25, Tables 101 and 108. PEM of 11,316 epilepsy patients identified seven cases of Stevens-Johnson syndrome (SJS) in adults, four on concomitant VPA.…”
Section: Lamotriginementioning
confidence: 99%
See 1 more Smart Citation
“…There was not a higher than expected incidence of spontaneous, missed or legal abortions, ectopic pregnancies, intra-uterine deaths or congenital abnormalities (Wilton et al, 1998). Goldstein & Sundell (1999) reviewed five prospective surveys and four published cohortcontrolled studies of women who received SSRIs during pregnancy.…”
Section: Pregnancymentioning
confidence: 99%
“…[5][6][7][8] PEM provides a numerator and a denominator over a known time frame: it permits, therefore the calculation of the incidence density for each reported event. Thus:…”
Section: Methodsmentioning
confidence: 99%